(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article is devoted to the consideration of the main models of Personnel Management. The study allows us to note that the problem of effective Personnel Management is the most pressing problems of the effectiveness of the organization. For Russia, this is relative. new problem. Its relevance assumes the study of accumulated domestic and foreign experience.